Instructional Leadership and 21st-Century Pedagogy: Predicting Students' Critical Thinking and Science Performance in Philippine Public Schools - Analyn G. Saucejo; Nhelbourne K. Mohammad (The Indonesian Institute of Science and Technology Research, 2026)
This study examined the predictive influence of school administrators' leadership and 21st-century science learning practices on Grade 9 students' critical thinking and academic performance in science. A quantitative, descriptive-correlational design with a predictive component was employed in 58 public junior high schools in the Zamboanga del Norte Division, Philippines. Data were collected from 58 school administrators, 89 Grade 9 science teachers, and 340 Grade 9 students using validated questionnaires, a critical thinking test, and official school records. Findings revealed that administrators' leadership was